Interaction of the main active components in Shengmai formula mediated by organic anion transporter 1 (OAT1). (5th October 2022) - Hou, Jinxia; Zhong, Lanping; Liu, Jianming; Liu, Fanglan; Xia, Chunhua
Abstract: Ethnopharmacological relevance: Shengmai formula (SMF) is a classical traditional Chinese medicine prescription, which is widely used in the treatment of cardiovascular and cerebrovascular diseases. Our previous studies have demonstrated that some components in SMF can interact with each other through breast cancer resistance protein, sodium taurocholate co-transporting polypeptide, organic anion transporting polypeptide 1B1 and 1B3. Organic anion transporter 1 (OAT1) is highly expressed in kidney, mediating the elimination of many endogenous and exogenous substances. However, the interaction between the main active components in SMF and OAT1 is not clear. Aim of the study: This study aimed to investigate the interactions of the major bioactive components in SMF mediated by OAT1. Materials and methods: Four main fractions, namely, ginseng total saponins (GTS), ophiopogon total saponins (OTS), ophiopogon total flavonoids (OTF), fructus schisandrae total lignans (STL), and 12 active components, namely, ginsenoside Rg1, Re, Rd and Rb1, ophiopogonin D and Dˊ, methylophiopogonanone A and B, schizandrol A and B, schizandrin A and B, were selected to explore the interactions of SMF with OAT1 using cell and rat models. Results: The above four main fractions in SMF all exhibited inhibitory effects on the uptake of 6-carboxyfluorescein (6-CF), a classic substrate of OAT1. Among the 12 main effective components, only ginsenoside Re, Rd, and methylophiopogonanone A showed inhibition of 6-CF uptake. Additionally, we found that schizandrin B was transported by HEK293-OAT1 cells, and schizandrin B uptake was markedly inhibited by GTS, OTS, OTF, ginsenoside Re, Rd, and methylophiopogonanone A. In rats, ginsenoside Re, Rd, and methylophiopogonanone A jointly increased the AUC(0-t), AUC(0-∞), and Cmax of schizandrin B, but they decreased its clearance in plasma and excretion in urine. Conclusions: Ginsenoside Re, Rd, and methylophiopogonanone A were the potential inhibitors of OAT1, and may interact with some drugs serving as OAT1 substrates clinically. Schizandrin B was a potential OAT1 substrate, and its OAT1-mediated transport was inhibited by ginsenoside Re, Rd, and methylophiopogonanone A. OAT1-mediated interactions of the main active components in SMF can be regarded as one of the important compatibility mechanisms of traditional Chinese medicine preparations. Graphical abstract: Image 1